2018
DOI: 10.1130/g45285.1
|View full text |Cite
|
Sign up to set email alerts
|

A honeycomb seafloor morphology in carbonate sediment of the Carnegie Ridge (offshore Ecuador): Formation and potential geodynamic significance

Abstract: Based on swath bathymetry, two-dimensional, high-resolution seismic reflection profiles, and Ocean Drilling Program/Deep Sea Drilling Project (ODP/DSDP) data, we describe a seafloor honeycomb pattern and propose a model for its formation in Pliocene-Miocene Page 2 of 27 carbonate deposited on the uneven oceanic basement of the Carnegie Ridge (offshore Ecuador). Hydrothermal fluids derived from the basement aquifer fractured and dissolved carbonate sediment, creating seafloor pits above basements highs. Fluids … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 21 publications
2
20
0
1
Order By: Relevance
“…It also suggests that the fractures could be the fault planes of a creeping process, which would result in the rippled morphology. Similar dissolution morphologies along with internal creeping of the sedimentary infill have been found in Carnegie Ridge (Michaud et al, 2018). Beneath the current sedimentary infill there are numerous reverse blind faults which one in the middle slope could act currently as transcurrent blind faults since the canyon networks show slightly laterally displacement ( Figs.…”
Section: Seismicity and Kinematics Of The Ocdsupporting
confidence: 70%
“…It also suggests that the fractures could be the fault planes of a creeping process, which would result in the rippled morphology. Similar dissolution morphologies along with internal creeping of the sedimentary infill have been found in Carnegie Ridge (Michaud et al, 2018). Beneath the current sedimentary infill there are numerous reverse blind faults which one in the middle slope could act currently as transcurrent blind faults since the canyon networks show slightly laterally displacement ( Figs.…”
Section: Seismicity and Kinematics Of The Ocdsupporting
confidence: 70%
“…In a follow‐up study, Michaud et al. (2018) concluded that the seafloor depressions formed through a combination of fluid‐flow, carbonate dissolution and current scouring. Villinger et al.…”
Section: Geologic Backgroundmentioning
confidence: 99%
“…Almost all suggested origins involve movement of fluids and/or gas through the sedimentary section and bottom currents leading to erosional processes, but in unknown ways. Possible explanations include submarine dissolution (Bertoni & Cartwright, 2005; Lonsdale & Fornari, 1980; Michaud et al., 2005; Villinger et al., 2017), silica diagenesis (Davies, 2005), slope instability (Pilcher & Argent, 2007), a combination of fluid flow and bottom currents (Betzler et al., 2011; Michaud et al., 2018; Sun et al., 2011), thermogenic degassing related to volcanic activity (Collins et al., 2011), or destabilization of methane hydrate (Davy et al., 2010; Hill et al., 2004). These different processes have different implications for physical, chemical, mechanical, and thermal properties of the upper crust, as well as hydrogeology and the biosphere (Tryon e al., 2001).…”
Section: Introductionmentioning
confidence: 99%
“…This oblique subduction, which involves the Carnegie Ridge (a 2-km-high and 200-km-wide volcanic ridge) resulting from the eastward motion of the Nazca plate over the Galapagos hotspot since ca 20 Ma (Sallarès et al, 2003), is thought to control the northeastward motion of the North Andean Silver (Witt and Bourgois, 2010), the subsequent opening of the Gulf of Guayaquil (Witt et al, 2006), and the Ecuadorian forearc uplift (Pedoja et al, 2006;Fig.1). The timing of the ridge subduction onset is highly debated ranging from 1 to 15 Ma (Lonsdale and Klitgord, 1978;Spikings et al, 2001;Michaud et al, 2009;Collot et al, 2009;Schütte et al, 2010;Spikings and Simpson, 2014;Michaud et al, 2018;Chiaradia et al, 2020). Several authors argue for an initiation of the Carnegie Ridge-trench interaction as early as ~10-15 Ma.…”
Section: Geodynamic Frameworkmentioning
confidence: 99%
“…In Ecuador, the subduction age for the Carnegie Ridge is controversial (Michaud et al, 2009) and the morphology of the ridge subducted part is unknown and could have been much different of what is currently observed. On the Nazca plate, the Carnegie Ridge exhibits in its midst a topographic low (saddle) at 2400-m depth (Michaud et al, 2018), meanwhile the segment which is close to the trench is at 700 m depth. Indeed, substantial along-strike relief differences along the volcanic aseismic ridges are currently observed and when they enter into subduction, they could produce different magnitudes of deformation in the forearc.…”
Section: Geodynamic Control Of the Coastal Cordillera Exhumationmentioning
confidence: 99%